Making trauma registries more useful for improving patient care: A survey of trauma care and trauma registry stakeholders across Australia and New Zealand. Issue 10 (October 2021) - O'Reilly, Gerard M.; Fitzgerald, Mark C.; Curtis, Kate; Mathew, Joseph K
Highlights: The main current use and priority for single site trauma registries across Australia and New Zealand was to inform the quality improvement program. For the Australia New Zealand Trauma Registry, the main current use was periodic reporting and the main priority was benchmarking. Regardless of the registry level and potential uses there was a consistently clear wish to better use trauma registries. The most highly ranked priority outcome for trauma care stakeholders was preventable death, followed by missed injury and quality of life. Abstract: Introduction: Injury is a major global health burden. Trauma registries have been used for decades to monitor the burden of injury and inform trauma care. However, the extent to which trauma registries have fulfilled their potential remains uncertain. The aims of this study were to determine the current and priority uses of trauma registries across Australia and New Zealand and to establish the priority clinical outcomes, the probability for which, if known for an individual trauma patient, would better inform that same patient's care, during hospital admission. Methods: A prospective observational study using survey methodology was conducted. Participants were sourced from the Australia New Zealand Trauma Registry (ATR) participating hospitals. The survey questions included: the current uses and priorities for both single-site trauma registries and the binational trauma registry; the five top-ranked priority outcomes for which knowing the probability, for an individual patient, would inform care; and the priority timepoints for applying patient-level outcome prediction models. Results: Of the 26 ATR-participating hospitals, 25 were represented by a total of 54 participants in the survey, including trauma service directors and trauma nurse coordinators. The main trauma registry use and priority for the single site registries was to inform the quality improvement program; for the ATR, the main use was periodic reporting and the main priority was benchmarking. For each potential purpose of the registry, the future priority level was ranked more highly than the current level of utilisation. The most highly ranked priority patient-level outcomes requiring prediction were: preventable death, missed injury, quality of life, admission costs, pulmonary embolism, post-traumatic stress disorder, length of hospital stay, errors in decision-making and deep venous thrombosis. The time period between leaving the emergency department and the 24 h mark following presentation was considered the preferred time for patient-level priority outcome prediction. Conclusion: There is a mismatch between current trauma registry uses and future priorities. The priority outcomes demanding prediction in the first 24 h of a trauma patient's stay are preventable death, missed injury, quality of life, hospital costs, thromboembolism, post-traumatic stress disorder, length of hospital stay and errors in clinical decision-making.